2019
DOI: 10.1038/s41598-019-42920-5
|View full text |Cite
|
Sign up to set email alerts
|

I-BEAT: Ultrasonic method for online measurement of the energy distribution of a single ion bunch

Abstract: The shape of a wave carries all information about the spatial and temporal structure of its source, given that the medium and its properties are known. Most modern imaging methods seek to utilize this nature of waves originating from Huygens’ principle. We discuss the retrieval of the complete kinetic energy distribution from the acoustic trace that is recorded when a short ion bunch deposits its energy in water. This novel method, which we refer to as Ion-Bunch Energy Acoustic Tracing (I-BEAT), is a refinemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…A tailored compact monitor of this sort can be calibrated to a certain ion species for energy measurements. It has been demonstrated that even the energy distribution of a single ion bunch can be reconstructed from the ionoacoustic signal shape using a novel technique (called I-BEAT), that makes further use of the detector transfer function [12]. To replace an accelerator trigger, an appropriate scintillation detector can be used in transmission or attached to the monitor looking for prompt reaction gammas [9].…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…A tailored compact monitor of this sort can be calibrated to a certain ion species for energy measurements. It has been demonstrated that even the energy distribution of a single ion bunch can be reconstructed from the ionoacoustic signal shape using a novel technique (called I-BEAT), that makes further use of the detector transfer function [12]. To replace an accelerator trigger, an appropriate scintillation detector can be used in transmission or attached to the monitor looking for prompt reaction gammas [9].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Acoustic detectors can take advantage of their huge dynamic range and moreover, the acoustic signal is separated from the EMP due to the longer transit time of the sound wave. This has recently been demonstrated for energetic protons accelerated by state-of-the-art PW class lasers, where the typically broad energy distribution of a single polyenergetic proton bunch was reconstructed using the ultrasound signal from a single piezo-composite (PZT) transducer [12]. Moreover, acoustic signals from GeV heavy ions have been studied at accelerators in various experimental configurations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned approaches, in vivo range/dose verification utilizing proton‐induced acoustic (protoacoustic) signals is a very promising alternative solution. Since the concept was initially proposed by Askaryan, many groups have worked on a number of aspects including both numerical simulations and experimental measurements . Sulak et al experimentally detected acoustic signals produced by proton beams in fluid media and successfully demonstrated a thermal expansion model for this phenomenon .…”
Section: Introductionmentioning
confidence: 99%
“…In PBT applications, several simulation-based studies have been performed, focusing on analysis in a simple water medium [10][11][12][13] and in prostate and liver cancer patients 14 . Moreover, experimental studies have been performed, and positive results have been demonstrated using a linac 15 , a tandem accelerator 16 , a synchrotron [17][18][19][20] , laser-plasma accelerator 21 , and clinical-use accelerators, such as an isochronous cyclotron 22 and a synchrocyclotron 23 . However, compared to PET and PG detection, the use of the ionoacoustic wave detection has not been much explored because of the weakness of the pressure wave (of the order of millipascals) available during clinical beam delivery 22 .…”
mentioning
confidence: 99%